The Effect of Decreased Antipseudomonal Drug Consumption on Pseudomonas aeruginosa Incidence and Antimicrobial Susceptibility Profiles over 9 Years in a Lebanese Tertiary Care Center - Rima El-Basst; Sanaa Saliba; Lama Saleh; Nicolas Saoud; Eid Azar; Pierre Zalloua; Amanda Chamieh (MDPI AG, 2023)
Pseudomonas aeruginosa (PAE) is intrinsically resistant to numerous classes of antimicrobials such as tetracycline and β-lactam antibiotics. More epidemiological surveillance studies on the antimicrobial susceptibility profiles of PAE are needed to generate clinically significant data and better guided therapeutic options. We describe and analyze in a retrospective study the epidemiologic trends of 1827 Pseudomonas spp. isolates (83.5% PAE, 16.4% Pseudomonas sp., and 0.2% Pseudomonas putida) from various clinical specimens with their resistance patterns to antimicrobial consumption at a tertiary medical center in Lebanon between January 2010 and December 2018. We report a significant drop in the incidence of PAE from sputum (p-value = 0.05), whereas bloodstream infection isolation density showed no trend over the study period. We also registered a minimal but statistically significant drop in resistance of Pseudomonas to certain antibiotics and a decrease in the consumption of antipseudomonal antibiotics (p-value < 0.001). Only 61 PAE isolates from a total of 1827 Pseudomonas cultures (3.33%) were difficult to treat, of which only one was a bacteremia. Interestingly, we found that the carbapenem susceptibility of Pseudomonas was unaffected by the decrease in their consumption. These results augur that antimicrobial pressure may not be the sole contributor to resistance emergence. Finally, antimicrobial stewardship seems to have a positive impact on nosocomial epidemiology.